Pengaruh Akuntabilitas,Transparansi, dan Kejelasan Sasaran Anggaran terhadap Efektivitas Pengelolaan Dana Desa se-Kecamatan Banjar, Kabupaten Buleleng - Sari Utami Ketut; Nyoman Ayu Wulan Trisna Dewi; Putu Yunartha Pradnyana Putra (Vokasi : Jurnal Riset Akuntansi, 2026)
This study aimed to examine in depth the effect of accountability, transparency, and clarity of budget targets on the effectiveness of village fund management in Banjar District, Buleleng Regency. This research employed a quantitative method with a sample of 102 respondents selected through purposive sampling from village officials across 17 villages. Data were collected through questionnaires and analyzed using multiple linear regression to test the effect of each variable. The results showed that accountability, transparency, and clarity of budget targets had a positive and significant effect on the effectiveness of village fund management. These findings confirm that the implementation of accountability principles, information transparency, and clear budget target formulation are important factors in improving the effectiveness of village fund management. This study is expected to provide empirical contributions for village governments in strengthening better financial governance and to serve as a reference for future research related to village fund management.